The challenges posed by equine arboviruses. (14th April 2018) - Chapman, G. E.; Baylis, M.; Archer, D.; Daly, J. M.
Summary: Equine populations worldwide are at increasing risk of infection by viruses transmitted by biting arthropods, including mosquitoes, biting midges ( Culicoides ), sandflies and ticks. These include the flaviviruses (Japanese encephalitis, West Nile and Murray Valley encephalitis), alphaviruses (eastern, western and Venezuelan encephalitis) and the orbiviruses (African horse sickness and equine encephalosis). This review provides an overview of the challenges faced in the surveillance, prevention and control of the major equine arboviruses, particularly in the context of these viruses emerging in new regions of the world.